2013
DOI: 10.3389/fonc.2013.00165
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Akt-mTOR Interactions

Abstract: The serine threonine protein kinase, Akt, is at the central hub of signaling pathways that regulates cell growth, differentiation, and survival. The reciprocal relation that exists between the two activating phosphorylation sites of Akt, T308 and S473, and the two mTOR complexes, C1 and C2, forms the central controlling hub that regulates these cellular functions. In our previous review “PI3Kinase (PI3K)-AKT-mTOR and Wnt signaling pathways in cell cycle” we discussed the reciprocal relation between mTORC1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 93 publications
8
109
0
3
Order By: Relevance
“…However, activation of p-Akt via mTOR2 signaling cascades is also involved in regulation of p-Akt (S473). Additionally, inhibition of mTOR1 by rapamycin derivatives increases mTOR2, resulting in activation of p-Akt (S473) (Sarbassov et al 2005;McDonald et al 2008;Breuleux et al 2009;Vadlakonda et al 2013). In line with this notion, attenuation of PTS noise-induced hearing loss with rapamycin may also be due in part to the activation of p-Akt (S473) (Yuan et al 2014, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…However, activation of p-Akt via mTOR2 signaling cascades is also involved in regulation of p-Akt (S473). Additionally, inhibition of mTOR1 by rapamycin derivatives increases mTOR2, resulting in activation of p-Akt (S473) (Sarbassov et al 2005;McDonald et al 2008;Breuleux et al 2009;Vadlakonda et al 2013). In line with this notion, attenuation of PTS noise-induced hearing loss with rapamycin may also be due in part to the activation of p-Akt (S473) (Yuan et al 2014, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of mTORC1 leads to stimulation of mTORC2, which positively regulates cell survival and proliferation at different signaling levels, mainly by the activation of AKT. 54 Apart from inhibition of EGFR phosphorylation, a decrease in the activation of mTOR could be caused by profound endocytosis of nanoparticles. Reports have shown that mTORC1 activation can be decreased during the failure of lysosome reformation.…”
Section: Nanoparticles Decrease Adhesiondependent Signaling Pathwaysmentioning
confidence: 99%
“…Cell cycle progression is regulated by Akt through indirect stabilization of cyclin D1 and Myc. Akt also stimulates protein synthesis and cell growth by activating the mammalian target of rapamycin (mTOR) pathway through the inhibition of the heterotrimeric complex consisting of tuberous sclerosis 1 or hamartin (TSC1) and tuberous sclerosis 2 or tuberin (TSC2) (Manning & Cantley 2007, Vadlakonda et al 2013.…”
Section: Pi3k/pten/akt and Tsc/mtor Pathwaysmentioning
confidence: 99%